Discussing Drug Use With Health Care Providers Is Associated With Perceived Need and Receipt of Drug Treatment Among Adults in the United States: We Need to Talk. Issue 7 (July 2020) - Mauro, Pia M.; Samples, Hillary; Klein, Kathryn S.; Martins, Silvia S.
Abstract : Background: Drug treatment utilization is low despite a high public health burden of drug use disorders (DUDs). Engaging people at risk for DUDs across a broader range of health care settings may improve uptake of drug treatment. Objectives: To estimate the prevalence of drug use screening/discussions between health care providers and individuals with past-year drug use, and to assess the associations between drug use screening/discussions and perceived need and use of drug treatment. Methods: We analyzed representative cross-sectional data from the 2015 to 2017 National Surveys on Drug Use and Health. The sample included adults aged 18 years and above reporting past-year drug use and ≥1 health care visit. We measured correlates of drug use screening/discussions using multinomial logistic regression. Overall and among adults meeting DUD criteria, we used logistic regression to estimate associations between drug use screening/discussions and (1) past-year drug treatment and (2) perceived need for treatment. Results: In the full sample (n=21, 505), 34.50% reported no screening/discussions, 44.50% reported screening only, and 21.00% reported discussions with providers. Discussions were associated with significantly higher odds of receiving any drug treatment [adjusted odds ratio (aOR)=3.52 (2.66–4.65)], specialty drug treatment [aOR=4.13 (2.92–5.82)], and perceived treatment need [aOR=2.08 (1.21–3.59)]. Among people with DUD (n=3, 834; 15.69%), discussions were associated with treatment use, but not with perceived need. Conclusions: Discussing drug use with providers may impact people's perceptions of drug treatment need and use, indicating potential opportunities to engage people in addiction treatment. Addressing barriers to discussing drug use across care settings could increase treatment use, particularly among people with DUD. Abstract : Supplemental Digital Content is available in the text.